2007
DOI: 10.1089/jir.2007.0013
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Interferon Regulatory Factor-1 Promoter Are Not Associated with Psoriasis and Do Not Influence IFN-α-Induced Th1 Polarization

Abstract: Psoriasis is a chronic inflammatory skin disease, characterized by a Th1 cytokine profile. We previously demonstrated that type I interferon (IFN-alpha/beta) signaling is activated in psoriatic skin. Type I IFNs regulate the expression of many proinflammatory and anti-inflammatory cytokines, resulting in Th1 polarization. We assessed whether peripheral blood mononuclear cells (PBMC) from psoriatic patients show aberrant IFN-alpha responses. IFN-alpha stimulation caused a similar enhancement of IFN-gamma and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…CXCL2 that has function in immune response is over-expressed in osteoarthritis fibroblasts rather than rheumatoid fibroblasts [47], up-regulated in psoriatic epidermis [48], and also in epithelial tissue [49]. IL10 is expressed in PBMCs of psoriasis [50], RA [51] and IBD patients [52]. The expression of NAMPT which is a pre-B cell-enhancing factor is increased in colonic biopsy specimens of IBD patients compared to healthy controls [53], it is also up-regulated in plasma and synovial fluid of RA patients [54]; and in PBMC of psoriasis in the diseased stage [10].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL2 that has function in immune response is over-expressed in osteoarthritis fibroblasts rather than rheumatoid fibroblasts [47], up-regulated in psoriatic epidermis [48], and also in epithelial tissue [49]. IL10 is expressed in PBMCs of psoriasis [50], RA [51] and IBD patients [52]. The expression of NAMPT which is a pre-B cell-enhancing factor is increased in colonic biopsy specimens of IBD patients compared to healthy controls [53], it is also up-regulated in plasma and synovial fluid of RA patients [54]; and in PBMC of psoriasis in the diseased stage [10].…”
Section: Discussionmentioning
confidence: 99%
“…IRF1 is one of the transcription factors regulating type I IFN responses. Although SNPs of the IRF1 promoter may be related to the T-helper type 1 (Th1) response in chronic hepatitis C infection 38 , studies have found no association between SNPs of the IRF1 promoter and the pathogenesis of psoriasis 39 . IRF1 has been observed throughout the epidermis in both normal skin and psoriatic lesions 40 , but one study reported that IRF1 expression is lower in psoriatic lesions than in non-lesions of patients with psoriasis or normal skin.…”
Section: Irfs and Psoriasismentioning
confidence: 99%